2016
DOI: 10.18632/oncotarget.11839
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin G induce apoptosis and autophagy in human nasopharyngeal cancer cells by modulation of AKT and mitogen-activated protein kinase pathways in vitro and in vivo

Abstract: Polyphyllin G (also call polyphyllin VII), extract from rhizomes of Paris yunnanensis Franch, has been demonstrated to have strong anticancer activities in a wide variety of human cancer cell lines. Previous studies found that Polyphyllin G induced apoptotic cell death in human hepatoblastoma cancer and lung cancer cells. However, the underlying mechanisms of autophagy in human nasopharyngeal carcinoma (NPC) remain unclear. In this study, Polyphyllin G can potently induced apoptosis dependent on the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 45 publications
3
71
0
Order By: Relevance
“…Zhang et al found that PS VII inhibited MAPK signaling pathway to have its strong antiinflammatory effects on different in vitro and in vivo models . Moreover, PS VII was found able to induce apoptosis of nasopharyngeal carcinoma cells by activating ERK, while AKT and p38 MAPK were responsible for PS VII‐induced autophagy . Not surprisingly, PS VII‐treated HepG2/ADR cells in this work also exhibited the reduced p‐PI3K, p‐AKT, and p‐p38 in a concentration‐dependent manner, suggesting that PS VII may inhibit PI3K/AKT/MAPK signaling pathway to reverse the drug resistance of HCC HepG2/ADR cells to ADR.…”
Section: Discussionsupporting
confidence: 53%
“…Zhang et al found that PS VII inhibited MAPK signaling pathway to have its strong antiinflammatory effects on different in vitro and in vivo models . Moreover, PS VII was found able to induce apoptosis of nasopharyngeal carcinoma cells by activating ERK, while AKT and p38 MAPK were responsible for PS VII‐induced autophagy . Not surprisingly, PS VII‐treated HepG2/ADR cells in this work also exhibited the reduced p‐PI3K, p‐AKT, and p‐p38 in a concentration‐dependent manner, suggesting that PS VII may inhibit PI3K/AKT/MAPK signaling pathway to reverse the drug resistance of HCC HepG2/ADR cells to ADR.…”
Section: Discussionsupporting
confidence: 53%
“…The MAPK signaling pathway is known as a stress-activated kinase, and it participates in the regulation of cellular responses [ 32 ]. MAPK has been shown to promote drug resistance and the regulation of p53, and Bcl-2 may activate MAPK to induce apoptosis [ 33 ]. STAT3 is correlated with poor prognosis in cancer patients and has been regarded as a specific target of cancer treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, cells were implanted onto six‐well overnight and then treated with different doses of coronarin D for 24 h. Cells were harvested and suspended in PBS (2% BSA), and then incubated with Muse Annexin V & Dead Cell reagent (EMD Millipore, Billerica, Massachusetts) for 20 min at room temperature in dark. Samples were analyzed by Muse Cell Analyzer flow cytometry and processed data by Muse Cell Soft V1.4.0.0 Analyzer Assays.…”
Section: Methodsmentioning
confidence: 99%